2017
DOI: 10.1098/rsos.160645
|View full text |Cite
|
Sign up to set email alerts
|

Body size–trophic position relationships among fishes of the lower Mekong basin

Abstract: Body size is frequently claimed to be a major determinant of animal trophic interactions, yet few studies have explored relationships between body size and trophic interactions in rivers, especially within the tropics. We examined relationships between body size and trophic position (TP) within fish assemblages in four lowland rivers of the Lower Mekong Basin in Cambodia. Stable isotope analysis (based on δ15N) was used to estimate TP of common fish species in each river, and species were classified according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…Jardine (2016) proposed that increasing body size would lead to a greater consumer biomass reliance on allochthonous material in freshwaters. This mechanism is supported by the strong land-water connectivity generally observed in inland aquatic ecosystems (Jardine 2016), which could decrease the trophic position of larger fish in freshwaters (Ou et al 2017). Allochthonous material in freshwater systems is mostly derived from terrestrial plant detritus rich in carbon compared to nutrients (Hecky et al 1993), especially at lower latitudes (Boyero et al 2017).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Jardine (2016) proposed that increasing body size would lead to a greater consumer biomass reliance on allochthonous material in freshwaters. This mechanism is supported by the strong land-water connectivity generally observed in inland aquatic ecosystems (Jardine 2016), which could decrease the trophic position of larger fish in freshwaters (Ou et al 2017). Allochthonous material in freshwater systems is mostly derived from terrestrial plant detritus rich in carbon compared to nutrients (Hecky et al 1993), especially at lower latitudes (Boyero et al 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Allochthonous material in freshwater systems is mostly derived from terrestrial plant detritus rich in carbon compared to nutrients (Hecky et al 1993), especially at lower latitudes (Boyero et al 2017). Therefore, the association among the higher relative species richness of omnivorous fish in tropical waters (González-Bergonzoni et al 2012), the higher reliance of large aquatic consumers on terrestrial carbon and the high availability of carbon-rich plant-derived allochthonous material in tropical freshwaters may help elucidate the lower trophic position of larger tropical freshwater fish species (Ou et al 2017), compared to their temperate counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…For the native fishes that co‐occurred in the downstream section of the study systems, it is likely that their coexistence within similar habitat conditions may be mediated by trophic niche differentiation mechanisms. Studies elsewhere have shown that lower reaches of rivers are characterised by high richness that is mediated by trophic diversification that allows different fishes to occupy different trophic positions (Guo et al, ; Ou et al, ). Secondly, the general absence in the Great Fish River's upper mainstem section of the E. anoplus , which was historically widespread (Laurenson & Hocutt, ), suggest the likely impact of the IBWT in influencing both habitat availability for this species, together with the proliferation of multiple non‐native fishes, which include generalist predators such as C. gariepinus (Kadye & Booth, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional data for foraging behavior, habitat, mobility and physiology of Tonle Sap species would help address these ideas, but body size (Ou et al. ) and seasonal feeding strategies are known to vary widely within fish functional groups from other tropical floodplains (Novakowski et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to forage across spatially complex habitats has also been linked to cognitive capacity (brain size) both within and among freshwater fish species (Edmunds et al 2016), suggesting there could be physiological limits on the types of habitats and resources used by fish. Additional data for foraging behavior, habitat, mobility and physiology of Tonle Sap species would help address these ideas, but body size (Ou et al 2017) and seasonal feeding strategies are known to vary widely within fish functional groups from other tropical floodplains (Novakowski et al 2008). While difficult to predict, the variable nature of seasonal foraging strategies therefore appear characteristic of fishes inhabiting these systems.…”
Section: Discussionmentioning
confidence: 99%